Historical views of solidarity the twentieth century: Development and international cooperation through Manos Unidas newsletters - Ruiz Simón, Esther (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The international relations policy of the countries for the Western bloc launched development cooperation policies in the mid-twentieth century. In Spain, from the 1950s onwards, NGDOs emerged and began to work in the field of development cooperation, among them Manos Unidas. The evolution of development and development cooperation activities itself was reflected in the different newsletters that were published by Manos Unidas and reflect the progress made in the different stages. This article analyses the development actions through the publications made by the NGDO Manos Unidas.